Supercritical fluid extraction of γ-Pyrones from Ammi visnaga L. fruits - Mokhtar Bishr; Mohamed El-Degwy; Mohammed Abdel Hady; Mohamed Amin; Osama Salama (SpringerOpen, 2018)
Extraction with supercritical fluid technique has proved to be effective in many applications including extraction and separation of various active principals from medicinal plants. It was used due to its advantages especially safety, specificity, selectivity and ease of component recovery.Ammi visnaga, L. belongs to the family Apiaceae. The fruits are used specifically for the treatment of kidney stones depending on its γ-Pyrones (mainly khellin and visnagin) [2]. The supercritical fluid extraction technique of khellin and visnagin was investigated and the operating conditions for their extraction were optimized. The effect of different pressure (150, 200, 300, 400 and 500 bars), temperature (35, 40, 45, 50 and 55 °C), and particle sizes of the raw material (0.5, 1, 1.4 mm and entire fruits) on the extract yield was studied under dynamic conditions for extraction for a run time of 90 min. Optimum supercritical extraction condition was found to be 200 bars at 45 °C and optimum particle size was found to be 1.4 mm. The yield is yellowish white bitter powder and measures 1.74% w/w relative to the dried weight of the fruits containing 38.414% w/w average γ-Pyrones content of which 29.4%w/w khellin, and 9.014%w/w visnagin.The obtained extracts were analyzed by reversed phase HPLC. Keywords: Ammi visnaga fruits, γ-Pyrones (khellin and visnagin), Supercritical fluid extraction and HPLC